Parenting Styles and Gender Role - Labial, Mona R. (JPAIR Multidisciplinary Research, 2009)
The study aimed to examine the dynamic relationship of parenting styles and gender roles. Baumrind’s parenting styles of permissiveness, authoritative and authoritarian were correlated with Pearson and Bales’ Functionalist Theory on Gender Roles that was classified either instrumentality or expressiveness. A quantitative survey method was used to gather data. Data were gathered from 988 students of Brokenshire College, Davao City, Philippines. Analysis of Variance (ANOVA) was used to analyze the data. Results showed that the fathers’ parenting styles significantly differ with instrumentality role and expressiveness role in the community and school. The parenting styles of the father that influence one’s perception on gender roles are the authoritarian and permissive type. The mothers’ parenting styles do not significantly differ with the respondents’ perception on gender roles. However, authoritarian and permissive parenting styles of the mother are viewed as significant factor for portrayal of gender roles.